The scalability challenge of the blockchain: a review - Rahiman, Musharaf Unissa; Alyaseen, Imad Fakhri Taha; Eljadi, Fardous Mohamed (Design for Scientific Renaissance, 2019)
The blockchain is an equivalently new innovation utilized for storing and verifying transaction records for online cryptocurrencies like Bitcoin. The framework is expandable and distributed, making it hard for transactions to be rehashed, copied, or faked. During the transaction process many unsolved issues have been noticed such as there is no data privacy as many blockchains are public and scalability. Scalability is an important concern to ensure large-scale adoption of blockchain systems. The throughput of a blockchain is limited if it grows linearly and peers are forced to execute transactions serially. This paper aims to provide an overview which outlines on the major challenge of the blockchain which is the scalability issue. Moreover, in order to assist the development process of new technologies the pros and cons of previous techniques used for improving the scalability challenges of the blockchain are summarised.